2019
DOI: 10.1007/s00402-019-03131-9
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for nonunion after intramedullary nailing of subtrochanteric femoral fractures

Abstract: Introduction Nonunion is a common complication after intramedullary nailing of subtrochanteric femoral fractures. A more detailed knowledge, particularly of avoidable risk factors for subtrochanteric fracture nonunion, is thus desired to develop strategies for reducing nonunion rates. The aim of the present study therefore was to analyse a wide range of parameters as potential risk factors for nonunion after intramedullary nailing of subtrochanteric fractures. Materials and methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 41 publications
3
46
1
6
Order By: Relevance
“…[ 47 ] Similarly, Krappinger et al recently demonstrated varus malalignment of greater than 5 degrees and loss of medial support were both significant risk factors for nonunion. [ 49 ] Peschiera et al examined a series of nonunions in distal femoral fractures and found varus alignment of the distal fragment of more than 5 degrees in greater than half of their nonunion cases. [ 45 ] This was attributed to medialization of the distal articular block—a common technical error with the use of a distal femoral locking plate.…”
Section: Section 2: Revising and Removing Hardwarementioning
confidence: 99%
“…[ 47 ] Similarly, Krappinger et al recently demonstrated varus malalignment of greater than 5 degrees and loss of medial support were both significant risk factors for nonunion. [ 49 ] Peschiera et al examined a series of nonunions in distal femoral fractures and found varus alignment of the distal fragment of more than 5 degrees in greater than half of their nonunion cases. [ 45 ] This was attributed to medialization of the distal articular block—a common technical error with the use of a distal femoral locking plate.…”
Section: Section 2: Revising and Removing Hardwarementioning
confidence: 99%
“…Krappinger et al studied risk factors for nonunion after intramedullary nailing of subtrochanteric fractures. In their study, neither open reduction nor the use of wire cerclage were significant risk factors for nonunion [ 10 ]. This is in contrast to malalignment, which has been shown to be a risk factor for nonunion [ 8 , 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…In their study, neither open reduction nor the use of wire cerclage were significant risk factors for nonunion [ 10 ]. This is in contrast to malalignment, which has been shown to be a risk factor for nonunion [ 8 , 9 , 10 ]. Kasha et al concluded that regardless of the method chosen, the key point to reduce the risk of complications is adequate reduction [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We are doubtful about the success of the surgical treatment because of the discordance in the fracture reduction between both hips. Subtrochanteric femoral fractures have higher nonunion rates compared with other anatomical regions besides atypical femur fracture (AFF) [2]. Risk factors for nonunion include varus malreduction, residual displacement after reduction, lack of medial cortical support, and bisphosphonateassociated fractures.…”
Section: Dear Editormentioning
confidence: 99%